FULL AUTOMATION IN ITS INFANCY: THE SITUATIONIST AVANT-GARDE BOOK FIN DE COPENHAGUE - Routhier, Dominique (The Nordic Journal of Aesthetics, 2020)
This article discusses Fin de Copenhague, a Situationist book experiment from 1957 by Asger Jorn and Guy Debord. By way of a contextualizing archival study with special attention to Jorn’s contemporaneous book project Pour la forme, the article demonstrates that the Russian avant-garde book was a key influence if also a point of critical departure. On this reading, Fin de Copenhague marks a turn away from the unbridled technological optimism of the historical avant-garde. In its material implications and aesthetic choices, Fin de Copenhague draws attention to crucial changes in the capitalist mode of production and challenges the then nascent discourse about “full automation.”